Analisis Yuridis terhadap Tindak Pidana Penganiayaan yang Mengakibatkan Cacat Permanen di Kabupaten Sikka : (Studi Kasus Putusan Nomor: 26/Pid.B/2022/PN.Mme) - Theresia Edelweis Putri Nurak; Aksi Sinurat; Orpa G. Manuain (Jurnal Hukum dan Sosial Politik, 2024)
In Decision Number: 26/Pid.B/2022/PN.Mme regarding abuse which resulted in permanent disability, the panel of judges only imposed a criminal sentence on the defendant with a prison sentence of 9 months. The problem to be studied is the basis for the consideration of the Panel of Judges and the imposition of the crime. This research aims to find out the basis for the judge's considerations and the imposition of crimes against perpetrators of abuse. The benefits of this research are theoretical and practical benefits. The type of research that will be used in this writing is a normative legal study. The types of research approaches used include the statutory approach, case approach, conceptual approach and comparative approach. The data sources used in this research use two data sources, namely primary legal materials and secondary legal materials. Whether or not the judge's decision is in accordance with the criminal act charged by the Public Prosecutor, the judge must consider aspects, namely juridical, philosophical and sociological aspects. The sentence imposed on perpetrators of torture is a maximum prison sentence of 5 years, in accordance with the contents of Article 351 paragraph (2) of the Criminal Code. The judge did not take into account the juridical, sociological and philosophical aspects as a basis for consideration in making decisions regarding Decision Number: 26/Pid.B/2022 /PN.Mme. The actual criminal sentence against the defendant is a maximum imprisonment of 5 (five) years), as stated in Article 351 paragraph (1) of the Criminal Code which states "If the action results in serious injury, the guilty person is threatened with a maximum prison sentence of five years".